Sterically congested boronate and silane synthesis via electronically controlled protoboration and protosilylation - Wang, Cheng-Qiang; Li, Yi; Feng, Chao (Cell reports physical science, 2021)
Multi-functionalized tertiary/secondary boronates and silanes have found wide applications in areas spanning organic synthesis, advanced material development, and pharmaceutical research. Effective access to these versatile motifs via protoboration/silylation of allenes remains unfulfilled. Capitalizing on the fluorine effects, here we report copper-catalyzed protoboration/silylation of gem-difluoroallenes, which shows an abnormal reactivity profile. In stark contrast to the conventional paradigms of allene functionalization reactions, which are often subjected to the steric-control mode for more facile reaction initiation on lower-substituted double bonds, the present reaction displays a virtually reversed regioselectivity for the more sterically congested π system. The synergistic LUMO-lowering perturbation and stabilization of nascent organocopper by fluorine substituents are deemed critical for guaranteeing the high fidelity of the present transformation. We not only apply this developed methodology to the late-stage modification of compounds derived from natural products but also highlight the utility of the obtained gem-difluoroalkenes in further synthetic elaborations. [Display omitted] Easy access to congested boronate/silane via protoboration/silylation of allenesEfficient synthesis of versatile and bioactive gem-difluoroallylboronates and silanesFluorine effects induced reversed regioselectivity for more congested π systemLate-stage modification of complex compounds and derivatization of obtained products Conventional paradigms of allene functionalization are often subject to steric control for more facile reaction initiation on lower-substituted double bonds. Wang et al. present, to the best of their knowledge, the first example of tertiary/secondary boronate/silane construction via copper-catalyzed protoboration/silylation of gem-difluoroallenes, which displays a reversed regioselectivity for the sterically more congested π system.